Review of the functions of state banks in the system of ensuring the financial stability of the banking system of Ukraine - Погореленко, Н. П. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
Taking into account the extremely important role of state banks for the development of the country (today, they are, in fact, create the banking market), there is a need to re-orient their activity content from generating systemic risk to generating systemic stability.Among the key components of financial stability highlighted by the central banks of the countries and which, using the tools of macro-prudential regulation, ensure the financial stability of the banking system, a special place is given to the ability of the latter to smoothly perform its functions. The effectiveness of such implementation is determined to be the prior condition for such operational continuity.For this purpose, methodical support is proposed for revising the functionality of Ukrainian state banks in terms of their efficiency, determined by the DEA model (Data Envelopment Analysis) with input parameters of customer funds, operating expenses, reserves for credit risks, and output parameters of interest income.The calculations of the performance indicators of state banks by the DEA model were made using DEAOS (Data Envelopment Analysis Online Software).The values of the efficiency indicator were calculated, the ranking of banks was conducted, and the optimal values of input and output parameters for inefficient banks were given. Recommendations were made to improve the efficiency of their activities: balancing the volume of customer funds with the volume of active operations; reducing operating expenses and reserves for credit risks by increasing the quality of loan portfolios.In conclusion, by using the DEA model it is possible not only to determine the measure of the efficiency of state-owned banks in the financial market, but also to make management decisions regarding the adjustment of the main indicators of their activities. This, ultimately, will contribute to raising the level of financial stability not only of state banks, but also of the entire banking system of Ukraine.